Chemotherapy and Targeted Agents in the Treatment of Elderly Patients with Metastatic Colorectal Cancer - Tuca, Albert (J Clin Med, 2020)
Colorectal cancer (CRC) is one of the main causes of cancer death in the elderly. The older patients constitute a heterogeneous group in terms of functional status, comorbidities, and aging-related conditions. Therefore, therapeutic decisions need to be individualized. Additionally, a higher toxicity risk comes from the fact that pharmacokinetics and pharmacodynamics of the drugs as well as the tissue tolerance can be altered with aging. Although the chemotherapy efficacy in metastatic colorectal cancer (mCRC) is similar for older and young patients, more toxicity is presented in the elderly. While the mono-chemotherapy provides the same benefit for young and older patients, doublets front-line chemotherapy improves progression-free survival (PFS) but not overall survival (OS) in the elderly. Furthermore, the benefit of the addition of bevacizumab to chemotherapy in older patients has been shown in several clinical trials, while the clinical data for the benefit of anti-epidermal growth factor antibodies are scarcer. Immunocheckpoint inhibitors could be an appropriate option for patients with microsatellite instability (MSI) tumors. A prior geriatric assessment is required before deciding the type of treatment in order to offer the best therapeutic option.